2011
DOI: 10.1038/jcbfm.2011.146
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced SUMOylation and SENP-1 Protein Levels following Oxygen and Glucose Deprivation in Neurones

Abstract: Here, we show that oxygen and glucose deprivation (OGD) causes increased small ubiquitin-like modifier (SUMO)-1 and SUMO-2/3 conjugation to substrate proteins in cultured hippocampal neurones. Surprisingly, the SUMO protease SENP-1, which removes SUMO from conjugated proteins, was also increased by OGD, suggesting that the neuronal response to OGD involves a complex interplay between SUMOylation and deSUMOylation. Importantly, decreasing global SUMOylation in cultured hippocampal neurones by overexpression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
65
0
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(74 citation statements)
references
References 16 publications
3
65
0
6
Order By: Relevance
“…Consistent with this notion, we previously found that acute hypoxic challenge induces membrane depolarization when rat CGN were studied in current-clamp mode (Plant et al, 2002). Indeed, chronic stressors that increase the level of SUMOylated proteins in cells (Shao et al, 2004), including the transcription factor HIF1a (Cheng et al, 2007), and modify global patterns of SUMOylation (Cimarosti et al, 2012) have been inferred to be cytoprotective in cases where gene regulation and protein turnover are altered to conserve energy (Henley et al, 2014). Thus, ground squirrel hibernation torpor, a model system for studying tissue protection during decreased blood flow and oxygen delivery, is associated with more SUMOylation in the brain, liver, and kidneys (Lee et al, 2007).…”
Section: Discussionsupporting
confidence: 50%
“…Consistent with this notion, we previously found that acute hypoxic challenge induces membrane depolarization when rat CGN were studied in current-clamp mode (Plant et al, 2002). Indeed, chronic stressors that increase the level of SUMOylated proteins in cells (Shao et al, 2004), including the transcription factor HIF1a (Cheng et al, 2007), and modify global patterns of SUMOylation (Cimarosti et al, 2012) have been inferred to be cytoprotective in cases where gene regulation and protein turnover are altered to conserve energy (Henley et al, 2014). Thus, ground squirrel hibernation torpor, a model system for studying tissue protection during decreased blood flow and oxygen delivery, is associated with more SUMOylation in the brain, liver, and kidneys (Lee et al, 2007).…”
Section: Discussionsupporting
confidence: 50%
“…In fact, elevated SUMO conjugation has been associated with neuroprotection, since its induction and suppression resulted in reduced and increased neuronal damage and infarction, respectively. [4][5][6] The implications of ubiquitin aggregation for the outcome of focal cerebral ischemia are not clear. However, our previous data suggest that the presence of ubiquitin aggregates may in fact indicate a greater potential for tissue viability in this setting.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Ubiquitin and SUMO attachment to proteins has the potential to influence protein stability, interaction and localization, and may therefore represent an effective way to rapidly adapt the cellular proteome to the changing, stressful environment after stroke. Indeed, elevated SUMO conjugation has been associated with neuroprotection, [4][5][6] while the role of increased ubiquitin accumulation in stroke outcome has not been clarified.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, studies suggested that protein SUMOylation is involved in ischemic tolerance [22,23] and may have a neuroprotective role in cultured neurons and transgenic mice brains [24,25]. However, the reasons why ischemic damage still occurs even though many proteins remain SUMOylated remain unknown.…”
Section: Discussionmentioning
confidence: 99%